(untitled) (e-Journal of Linguistics, 2025)
This paper aims at describing the multimodal discourse analysis of linguistic form and images in the “Explore Flores: Komodo Island” video. The study focuses on the ideational meaning and representational meaning of spoken texts and visual modes. This is a qualitative study that uses the Systemic Functional-Multimodal Discourse Analysis approach. The researchers gathered the information by capturing some shots of “Explore Flores: Komodo Island” video. The results showed that the “Explore Flores: Komodo Island” video is a video made by an individual private party that has both promotional and persuasive value. Based on the results of the ideational meaning analysis, the appearance of the participant as a dominant carrier indicates the clarity and firmness of the persuasive meaning of the video maker to protect the sea around Komodo island tourist spots. Representational meaning is explained through conceptual meaning and narrative meaning. Based on the conceptual meaning, the video describes the symbolic icons of the tourism spots in Komodo Island, Flores including its Komodo Dragons, the ocean, the sunset seen from Komodo Island and other magnificent natural scenery. Based on the narrative representation, action and reactional process dominate the promotional video. Action process is presented in various activities shown by the park guard and the visitors, meanwhile reactional process is shown by smile on the face of the children and woman who are visiting the Komodo Island to show happiness of being in the tourism spot. The study contributes significantly to the theory of multimodal discourse analysis viewed from the phenomena of spoken text and visual modes.